Use of large animal models to investigate Huntington's diseases - Sen Yan (Cell Regeneration, 2019)
Animal models that can mimic human diseases are the important tools for investigating the pathogenesis of the diseases and finding a way for treatment. There is no doubt that small animal models have provided a wealth of information regarding disease pathogenesis and also offered widely used tools to develop therapeutic strategies. Rodent models have been very valuable for investigators to understand the mechanisms underlying misfolded protein-mediated neuronal dysfunction and behavioral phenotypes in a variety of neurodegenerative diseases including Alzheimer's, Parkinson's, and Huntington's diseases (HD). However, most of genetically modified rodent models of these diseases lack the overt and selective neurodegeneration seen in the patient brains. Since large animals are more similar to humans than small animals and rodents, the large animal models are likely to mimic important neuropathological features in humans. Here we discuss the application of large animal models in neurodegenerative disease research with focus on the HD large animal models, aiming to provide insight into the application of animal models to study neurodegenerative diseases.